Peranan Green Economy Menjadi Strategi Dalam Memperbaiki Pemulihan Ekonomi Serta Multilateral - I Kadek Donny Wishanesta (Journal on Education, 2024)
The green economy concept is one of the global strategies related to social, economic, and environmental crises. Methodologically, conceptualizing, implementing, and critiquing the creation of a green economy paradigm towards society leads to the challenge of a global strategy that has the goal of sustainability, poverty alleviation, and inclusion of vulnerable social sectors. The influence of the green economy on the sustainability of life is still in the context of grahita. The purpose of this research is to determine the effect of the green economy on economic recovery and multilateral problems. This research is a descriptive research that uses a literature study type or approach. The results of the study reveal that the application of a green economy is capable of driving national economic recovery as well as problems in the multilateral sector. In order for a green economy to be realized for the country, policy makers must be supported by various parties so that a sustainable green economy is formed. A green economy also contributes to maintaining a healthy environment and shaping ecosystems appropriately for present and future generations.